2017
DOI: 10.1016/j.jaip.2016.11.020
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Eosinophilic Esophagitis in Pediatric Patients with IgE-Mediated Food Allergy

Abstract: BACKGROUND Eosinophilic esophagitis (EoE) is an allergic inflammatory disease that is triggered by food allergens and characterized by progressive esophageal dysfunction. Recently, EoE has been identified in patients undergoing oral immunotherapy (OIT) for IgE-mediated food allergy, suggesting an association. OBJECTIVE We sought to ascertain whether significant associations exist between IgE-mediated food allergies and EoE. METHODS Utilizing analysis of EMR data and manual chart review, we examined our sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
67
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(76 citation statements)
references
References 58 publications
5
67
0
4
Order By: Relevance
“…Recommendations in diagnostics, genetics, allergy testing, therapeutics and disease complications have been published by various work groups . Patients have high rates of concurrent food sensitivities, and it has been recently reported by Hill et al that 68% of EoE patients have IgE‐mediated food allergy . Elimination diet/amino‐acid feedings are one of the mainstays of treatment in young children .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recommendations in diagnostics, genetics, allergy testing, therapeutics and disease complications have been published by various work groups . Patients have high rates of concurrent food sensitivities, and it has been recently reported by Hill et al that 68% of EoE patients have IgE‐mediated food allergy . Elimination diet/amino‐acid feedings are one of the mainstays of treatment in young children .…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] Patients have high rates of concurrent food sensitivities, 5 and it has been recently reported by Hill et al that 68% of EoE patients have IgE-mediated food allergy. 6 Elimination diet/ amino-acid feedings are one of the mainstays of treatment in young children. 7 Diagnostic criteria for other EGIDS, including eosinophilic gastritis, are less well defined, but Caldwell et al 8 neous immunotherapy (EPIT) in peanut allergic children, 9 we have decided to investigate the impact of EPIT on EGIDs.…”
Section: Introductionmentioning
confidence: 99%
“…Наиболее часто в качестве причинно-значимых продуктов выступают молоко, соя, яйца, зерновые, различные виды мяса [26].…”
Section: Ige-опосредованная гастроинтестинальная пищевая аллергияunclassified
“…96-4.62). Using a large pediatric virtual birth cohort, we have measured these risk relationships in individuals revealed that history of AD (hazard ratio [HR] 3.2, 95% confidence interval [CI] 2.2-4.6), IgE-mediated food allergy (IgE-FA; HR 9.1, 95% CI 6.5-12.6), and asthma (HR 1.9, 95% CI 1.3-2.7) are independently and cumulatively associated with subsequent EoE diagnosis (Table 1) [11].The relationship between IgE-FA and EoE is particularly strongchildren with IgE-FA develop EoE at 9 times the rate of children without IgE-FA [12]. IgE-FA and EoE have…”
mentioning
confidence: 99%
“…The relationship between IgE-FA and EoE is particularly strongchildren with IgE-FA develop EoE at 9 times the rate of children without IgE-FA [12]. IgE-FA and EoE have…”
mentioning
confidence: 99%